A Comparison of Mercury Biomagnification through Lacustrine Food Webs Supporting Brook Trout (Salvelinus fontinalis) and Other Salmonid Fishes - Finley, Monica L. D.; Kidd, Karen A.; Curry, R. Allen; Lescord, Gretchen L.; Clayden, Meredith G.; O'Driscoll, Nelson J. (Frontiers in Environmental Science, 2016)
Methyl mercury (MeHg) bioaccumulation in lower-trophic-level organisms and its subsequent biomagnification through food webs differs in magnitude among lakes and results in intraspecific variability of MeHg in top predator fishes. Understanding these differences is critical given the reproductive and neurotoxic effects of MeHg on fishes and their predators, including humans. In this study we characterized the food webs of five lakes in New Brunswick, Canada, supporting Brook Trout (Salvelinus fontinalis) using measures of relative trophic position (δ15N) and carbon sources (δ13C), determined the concentrations of MeHg in invertebrates and total Hg (THg) in fishes, and quantified MeHg biomagnification from primary to tertiary consumers. Methyl Hg and THg concentrations were highest in biota from lakes with lower pH. The trophic magnification slopes (TMS; log Hg versus δ15N) varied significantly among lakes (0.12-0.20; ANCOVA, p=0.031). When combined with data from other salmonid lakes in temperate and Arctic Canada (n=36), among-system variability in TMS was best, but weakly, positively predicted by aqueous total phosphorous (p = 0.028, R2adj = 0.109). These results suggest that lake productivity directly or indirectly influences the biomagnification of MeHg through diverse food webs supporting salmonids.